Deskripsi Percakapan Kritis Matematis Siswa dalam Pembelajaran Socrates Saintifik - Deta Marlita; Tina Yunarti; Widyastuti Widyastuti (Limacon: Journal of Mathematics Education, 2019)
This qualitative research aimed to describe the critical mathematical discourses in Socrates' scientific learning. The subjects of this study were 9 students of class VII-2 of SMP Global Madani Bandar Lampung in the academic year 2018/2019 who were chosen purposively. Then, 9 students were selected as research subjects consisting of three students with high, medium, and low mathematical abilities. This research data was qualitative data about students’ critical mathematical discourses obtained through observation, interviews, and documentations. Furthermore, data analysis was carried out through three stages, namely data reduction, data display, and conclusion drawing. Based on the results of the study, it was concluded that: (1) The students’ critical mathematical discourses that occurred in Socrates scientific learning more dominantly led to indicators of students’ critical thinking abilities, namely interpretation and analysis, (2) Students’ mathematical critical discourses appeared more often when the teacher asked Socrates questions of type of clarification and the reasons and evidence of the investigation, (3) Students’ mathematical critical discourses were more dominant when students do the scientific stages of associating and communicating.